Application of Target Costing To Reduce Production Costs And Increase Profits at CV. Tiga Putra Perkasa - Gabriella Anatasya Maria KAROUWAN; Stanly W. ALEXANDER; Natalia Y. T. GERUNGAI (Journal of Governance, Taxation and Auditing, 2023)
Target Costing is a method or strategy that allows companies to target product costs based on the selling price expected by consumers. This study aims to determine whether the application of target costing can be a tool to reduce production costs and increase profits at CV. Tiga Putra Perkasa. The analysis method used in this research is descriptive qualitative analysis. Namely, data collected through interviews and then described, and the type of research used is descriptive qualitative. This research will describe the application of target costing to CV. Tiga Putra Perkasa to compare production costs and profits obtained before and after implementing target costing. The company can save production costs of Rp 7,456,700. The results of this research showed that the impact on the increase in profits earned by the company from 37.4% before the application of target costing can increase to 42.7%, which shows that the company's expected profit target of more than 40% can be achieved by using target costing. The research results show that the company can reduce production costs so that the profit increase reaches 5% using target costing